What Bothers Innovation in China: Is It Only a Question of Counterfeits? - Yajie Zhao (Nordic Journal of Commercial Law, 2014)
Starting with a comparison of litigation data between Western litigants and Chinese officials on both public and private level, this article stands in the shoes of the foreign intellectual property (IP) right holders asking why a sound made by western society resonates so differently in China? This is done through the eyes of the Chinese adjudicators and the system as a whole: where, how long and with what results. It briefly lists various characteristics of each litigation phase that foreign IP right holders will confront, when choosing the Chinese judiciary (private litigation) to enforce their IP rights, especially patents. Insum, this article offers a picture, from the perspective of aprivate party, of procedural peculiarities of Chinese courts, the time limit system and compensation rules. Even though the Chinese government, at the federal level, is workiing very hard to introduce a positive image relating to private enforcement of IP rights, this article emphasizes that the negative attitude towards foreign right holders, , is caused by a normative chain effect. It is neither only about law nor only about policy.